ChemInform Abstract: Electroplated Bimagnetic Microwires: From Processing to Magnetic Properties and Sensor Devices. Issue 7 (18th February 2014) - Torrejon, Jacob; Infante, German; Badini‐Confalonieri, Giovanni; Pirota, Kleber R.; Vazquez, Manuel
Abstract Review: 87 refs.